Needs assessment in patients with inflammatory bowel disease in the encounter and communication with healthcare professionals: A fieldwork study - Fallesen, Janni Petersen; Krogh, Marie Louise; Minet, Lisbeth Rosenbek; Skjøth, Mette Maria; Knudsen, Torben; Kjeldsen, Jens (Journal of clinical nursing, 2023)
AimTo explore how patients with Inflammatory bowel disease experienced encounters with healthcare professionals in two gastrointestinal outpatient clinics to demonstrate what matters in the communication between patients and healthcare professionals.DesignThis fieldwork study is part of a larger study developing an application for patients with inflammatory bowel disease in a framework inspired by Participatory Design. Participatory design consists of three phases and this study focused on the first phase, needs assessment. A phenomenological hermeneutic approach and qualitative methods were applied to obtain an understanding of patients' needs.MethodsThree weeks of participant observations and three focus groups with 14 subjects were conducted at two university hospitals in Denmark. Field notes and interview transcripts were analysed using condensation of meaning and interpreted based on interactional nursing practice theory. The reporting method adhered to the EQUATOR guideline: COREQ.ResultsFour themes emerged: Easy and dependable access to healthcare professionals. Predictability of follow‐up appointments. Importance of privacy during patient exams and Quality of time spent with healthcare professionals.ConclusionEasy, dependable access, privacy, presence and predictability of follow‐up appointments were important to patients with Inflammatory Bowel Disease.Implications for the profession and patient careIn communication with patients with inflammatory bowel disease, healthcare professionals must be aware of privacy and the importance of predictable follow‐up agreements. They must be aware that presence and easy, reliable access positively affect patients' self‐care skills.Patient contributionThis study is part of a larger project based on Participatory design involving patients and healthcare professionals in the development of technology to support communication.